Playful Religion: An Innovative Approach to Prevent Radicalisation of Muslim Youth in Europe - Omer Gurlesin; Muhammed Akdag; Alper Alasag; Ina ter Avest (Religions, 2020)
Radicalisation of Muslim youth is a hot item in the Netherlands. Deradicalisation is therefore high on the agenda. In our view, however, the deradicalisation processes begin at a moment ‘when it is too late to lock the stable door, because the horse has already bolted’. That is why our focus is on the prevention of radicalisation. In our contribution, we explore the concept of ‘radicalisation’ and inform the reader about deradicalisation programmes developed in the Netherlands and in Europe. The lack of success of these programmes challenges us to focus on ‘prevention’. In our view, a playful dialogical encounter in a safe space is a must in the approach of young people who are on the verge of radicalisation. The above-mentioned concepts of radicalisation, deradicalisation and prevention are presented in the first paragraph, followed by a discussion of de- and counter-radicalisation programmes in paragraph two. The third paragraph focuses on the prevention of radicalisation in education. Crucial here is a dialogical relationship between teachers and students, between the students themselves and within the students’ inner selves. This latter aspect is inspired by the theoretical framework of the dialogical self-theory, with its core concept of ‘multi-voicedness’ and ‘positioning of voices’. Special attention in the positioning process is given to resilience. The heart of this publication is dedicated to the re-invention of an age-old Islamic game: shaṭranj al-ʿārifīn’. In the fourth paragraph, we describe its origins and our adapted version of this game. Playing the game in pilot studies—a ‘serious play session’—increases young people’s awareness of religion and its positioning, resulting in strengthening resilience in their life orientation. In the concluding fifth paragraph, we state that our innovative, playful and theoretically well-framed approach is a promising module to be implemented in formal and informal education.